2009
DOI: 10.1016/j.chom.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The S. Typhimurium Effector SopE Induces Caspase-1 Activation in Stromal Cells to Initiate Gut Inflammation

Abstract: In the healthy intestinal mucosa, homeostasis between the immune system and commensal microflora prevents detrimental inflammatory responses. Infection with acute enteropathogens such as Salmonella enterica serovar Typhimurium disturbs this homeostasis and triggers inflammation, but the underlying mechanisms are poorly understood. We found that bacterial delivery or ectopic expression of the S. Typhimurium type III effector protein SopE, a known activator of host cellular Rho GTPases, led to proinflammatory ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(185 citation statements)
references
References 51 publications
4
181
0
Order By: Relevance
“…7,15,30,31 It has also been recently reported that S. Typhimurium can induce caspase 1-mediated death of stromal cells. 18 Considering that the proinflammatory cytokines IL-1 and IL-18 are substrates of caspase 1, being cleaved and activated during the caspase 1-mediated macrophage cell death, this mechanism of Salmonella-induced macrophage death is thought to be a significant proinflammatory mechanism during S. Typhimurium infection, and therefore it has been named pyroptosis, which can be triggered not only by S. Typhimurium but also by several infectious or noninfectious pathological stimuli. 2 The role of caspase 1 during S. Typhimurium infection has been studied in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…7,15,30,31 It has also been recently reported that S. Typhimurium can induce caspase 1-mediated death of stromal cells. 18 Considering that the proinflammatory cytokines IL-1 and IL-18 are substrates of caspase 1, being cleaved and activated during the caspase 1-mediated macrophage cell death, this mechanism of Salmonella-induced macrophage death is thought to be a significant proinflammatory mechanism during S. Typhimurium infection, and therefore it has been named pyroptosis, which can be triggered not only by S. Typhimurium but also by several infectious or noninfectious pathological stimuli. 2 The role of caspase 1 during S. Typhimurium infection has been studied in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…SopE activates several innate immune signaling pathways [124] and is of major importance for eliciting intestinal inflammation [229] through activation of caspase-1 in enterocytes [280]. Caspase-1 activation results in cleavage and secretion of IL-1β and IL-18, which are important for the inflammatory response.…”
Section: Sope and Sope2mentioning
confidence: 99%
“…5 In patients with NTS, diarrhea is a result of bacterial type III effector protein's activation of proinflammatory caspase-1 in the intestinal mucosa and to the subsequent secretion of the cytokine IL-1β. 28 Because diarrhea is a defense mechanism that depends on a healthy immune system, NTS bacteremia not associated with diarrhea quite possibly warrants an immunodeficiency evaluation. 27,29 HTN, and AF AF = atrial fibrillation; CAD = coronary artery disease; CHF = congestive heart failure; DM = diabetes mellitus; ESRD = endstage renal disease; F = female; HD = hemodialysis; HIV = human immunodeficiency virus; HTN = hypertension; ITP = idiopathic thrombocytopenic purpura; M = male; MI = myocardial infarction; PC = pericardiocentesis; RA = rheumatoid arthritis; RF = renal failure; SLE = systemic lupus erythematosus; TC = thoracentesis; WBC = white blood cell Recurrent Salmonella septicemia is an acquired immunodeficiency syndrome-defining illness.…”
Section: Immunodeficiencymentioning
confidence: 99%